Development of Android-Based Interactive Multimedia for Secondary School Physics Study - Yunita, Rizki; Gunawan, Gunawan; Harjono, Ahmad; Kosim, Kosim (Department of Physics Education, Universitas Mataram, 2023)
This research aims to produce valid and practical learning products for physics education. The developed learning products consist of interactive multimedia based on Android, lesson plans (RPP), and test instruments for the topic of elasticity in physics. This study follows a Research and Development (R&D) approach, adapting the 4D model developed by Thiagarajan. The research stages include defining, designing, developing, and disseminating. The research subjects were 32 students in grade XI. Data collection techniques involved validation sheets, student response questionnaires, and pretest and posttest sheets for assessing conceptual understanding. The validation results indicate that the learning products fall under high validity. The average scores of expert and practitioner validators were 3.49 and 3.67 for interactive multimedia based on Android, 3.48 and 3.69 for the lesson plans, and 3.38 and 3.81 for the test instruments, respectively. The analysis of the response questionnaires showed that the products were convenient, with an average percentage of 82.27%. Therefore, the developed learning products are valid and highly practical for secondary school physics activities.